Quantification of Dynamic 11C-Phenytoin PET Studies - Mansor, Mohd Syahir; Boellaard, Ronald; Froklage, Femke E.; Bakker, Esther D.M.; Yaqub, Maqsood; Voskuyl, Rob A.; Schwarte, Lothar A.; Verbeek, Joost; Windhorst, Albert D.; Lammertsma, Adriaan (Society of Nuclear Medicine, 2015)
The overexpression of P-glycoprotein (Pgp) is thought to be an important mechanism of pharmacoresistance in epilepsy. Recently, 11C-phenytoin has been evaluated preclinically as a tracer for Pgp. The aim of the present study was to assess the optimal plasma kinetic model for quantification of 11C-phenytoin studies in humans. Methods: Dynamic 11C-phenytoin PET scans of 6 healthy volunteers with arterial sampling were acquired twice on the same day and analyzed using single- and 2-tissue-compartment models with and without a blood volume parameter. Global and regional test– retest (TRT) variability was determined for both plasma to tissue rate constant (K1) and volume of distribution (VT). Results: According to the Akaike information criterion, the reversible single-tissue-compartment model with blood volume parameter was the preferred plasma input model. Mean TRT variability ranged from 1.5% to 16.9% for K1 and from 0.5% to 5.8% for VT. Larger volumes of interest showed better repeatabilities than smaller regions. A 45-min scan provided essentially the same K1 and VT values as a 60-min scan. Conclusion: A reversible single-tissue-compartment model with blood volume seems to be a good candidate model for quantification of dynamic 11C-phenytoin studies. Scan duration may be reduced to 45 min without notable loss of accuracy and precision of both K1 and VT, although this still needs to be confirmed under pathologic conditions.